1997
DOI: 10.1111/j.1346-8138.1997.tb02741.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatricoma with a Bullous Appearance

Abstract: A 15-year-old Japanese girl had an asymptomatic nodule on the right thigh of seven months' duration. The clinical appearance was similar to that of a bulla. There was a history of blunt trauma from dog scratch to the skin over the tumor shortly before tumor growth. Histopathological findings were consistent with pilomatricoma. In the overlying dermis, the collagen bundles were compressed to the tissue surrounding the tumor and the large space was seen. Around the tumor, some dilated endothelium-lined vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 5 publications
3
47
0
5
Order By: Relevance
“…Hata and Ito [1]reported that pinching trauma induced a bulla-like appearance, and Iioka et al [2]reported that the fluid in the dermis was lymphatic, and lymphatic vessel dilation was observed beside the tumor. Continuous mechanical stimulation around the hard pilomatrixoma gave an impetus to the lymphatic congestion and the lymphatic vessel dilation, which would induce the edema in the dermis [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Hata and Ito [1]reported that pinching trauma induced a bulla-like appearance, and Iioka et al [2]reported that the fluid in the dermis was lymphatic, and lymphatic vessel dilation was observed beside the tumor. Continuous mechanical stimulation around the hard pilomatrixoma gave an impetus to the lymphatic congestion and the lymphatic vessel dilation, which would induce the edema in the dermis [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Akarsu ve ark. Psödobüllöz anetodermik pilomatrikoma inflamatuvar hücre infiltrasyonu ile ilişkili genişlemiş lenfatik damarlar görülmektedir 1,[6][7][8][9][10][11][12] . İlk kez 1943 yılında tanımlanan ve tüm PM'lı olguların %2'sini oluşturan anetodermik form ise klinik olarak gevşek, sarkık veya kese benzeri bir lezyon şeklinde görülebileceği gibi, keloid veya hipertrofik sikatris benzeri ya da buruşuk ve oldukça katlantılı atrofik deriyle örtülü psödobüllöz görünümlü bir lezyon şeklinde de karşımıza çıkabilir.…”
Section: Discussionunclassified
“…PM'lı olgularda büllöz görünümün oluşum mekanizması tam olarak bilinmemekle birlikte temel olarak PM sert yapısının neden olduğu lenfatik obstrüksiyonun primer rol oynadığı düşünülmektedir. Bunun sonucunda oluşan lenfatik sıvı konjesyonu, lenfatik damarlarda dilatasyon, lenfatik sızıntı ve tümörü çevreleyen dermisteki ödem büllöz görüntüye neden olmaktadır [7][8][9] . Bununla birlikte literatürde mekanik irritasyon ve köpek tırmalaması ile ilişkili nadir olgu bildirileri de mevcuttur 9,11,12 .…”
Section: Discussionunclassified
See 2 more Smart Citations